PEMETAAN SUSEPTIBILITAS MAGNETIK ENDAPAN TANAH SUNGAI SAIL PEKANBARU - Salomo; Dati Oktavia Oktavia; Usman Malik (JOURNAL ONLINE OF PHYSICS, 2019)
Mapping the value of the sedimentary magnetic susceptibility along the Sail Pekanbaru river using Surfer 11 Software has been carried out. The sample consisted of 70 location points consisting of 35 right bank edges and 35 left bank edges. The sampling method uses the grid method. The results of the magnetic level calculation show a range of values ​​from 0,03% to 0,19%.The results of magnetic degree value mapping indicate that the magnetic degree obtained is getting higher from upstream to downstream. The results showed that the suseptibility magnetic value of sediment in the Sail Pekanbaru river ranged from 0,82 × 10-8 m3 / kg to 3,44 × 10-8 m3 / kg, based on this value it can be estimated that the main magnetic particles of the sample are in the Sail Pekanbaru river is ilmenit. The results of mapping the magnetic susceptibility values ​​and mass susceptibility values ​​of the samples indicate that the magnetic susceptibility in the Sail Pekanbaru river from upstream to downstream is less.